Karakteristik Konsumen pada Pengembangan Produk Baru Teh Herbal Ciplukan - Tumanggor, Lolo Nola; Wiyono, Sulistyodewi Nur; Renaldi, Eddy; Utami, Hesty Nurul (Universitas Galuh, 2026)
Ciplukan is an herbal plant rich in antioxidants and has the potential to lower blood sugar. Ciplukan can be developed into functional drinks such as herbal tea, but the utilization of ciplukan as a raw material for herbal tea is still not widely known by the public. This study aims to determine the characteristics of ciplukan herbal tea consumers. The research design used is quantitative research with survey research methods. The analytical tool used is descriptive statistical analysis and crosstabulation analysis. Sample withdrawal using convenience sampling technique with 104 respondents. The results showed that the characteristics of ciplukan herbal tea consumers in this study were dominated by women aged 19-29 years, with the latest education level of high school and most of them were housewives and monthly income was in the range of Rp1,500,000-Rp3,000,000. From consumption patterns, the majority of consumers consume tea 1-3 times per week while herbal tea 4-6 times per month with the aim of consuming herbal tea because of the health benefits.